The Impact of Providing Material and Non-Material Incentives on Employee Work Motivation (Study on the Automotive Industry in West Bandung) - I Budiarti; M Maryati; V Lavira (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Humans are the main mover in the company and employees are the company’s main wealth so they must be maintained properly. To maintain these employees, the company must provide rewards other than wages/salaries in the form of appropriate incentives to improve welfare. The purpose of this study was to determine the impact of providing incentives, both material and non-material, on employee work motivation in an automotive industry located in West Bandung. This research is empirical research that is descriptive with a quantitative approach. The types of data used are primary data and secondary data. The method used in this study is the census method of 44 employees. The research instrument uses material incentives, non-material incentives and work motivation. Data analysis includes validity test, reliability test, classical assumption test, and hypothesis test with multiple linear regression as the analysis tool using SPSS version 25 for windows. Based on the discussion of the results of this study, it was concluded that material incentives and non-material incentives had a positive influence on employee motivation